Cryo-polygeneration plant - a novel operation algorithm leveraging adaptive AI energy systems models for urban microgrids - Thangavelu, Sundar Raj (2025)
Cryo-Polygeneration is a quite sophisticated system that accounts for different energy generations comprising electricity, steam, hot and cold energy and more. However, the true challenge lies in operating these diverse energy systems in harmony to achieve the best performance and overall process objectives, mainly operation cost and energy efficiency. This study proposes a novel algorithm for optimizing operations of cryo-polygeneration systems, enabling precise scheduling and dispatch based on anticipated time-varying energy requirements or loads. By deriving optimal setpoints that minimize operating expenses, the algorithm addresses key operational objectives within this emerging field of cryo-polygeneration systems. Leveraging the power of AI, this study exploited the use of adaptive AI model of the distributed energy systems that offers high prediction accuracy due to minimal plant-model mismatch and also uncovers inherent benefits and limitations. The developed algorithm is applicable to both island and grid-connected polygeneration systems with power trading attributes. The workability of the proposed operation algorithm was demonstrated using a district-scale case study, which confirms the integration of multi-energy technologies and process flexibility helped to improve operational objectives greatly, resulting in a 32 to 51 % reduction in operation costs compared to the baseline. Ultimately, this novel operational algorithm presents a transformative solution for cryo-polygeneration plants, offering a reliable framework to promote sustainable energy resource management. The proposed operation algorithm can be easily implemented in the energy management system of cryo-polygeneration plants, facilitating more efficient and sustainable energy resource utilization.